Formative assessment and feedback as learning tools in health professions education - Borges, Marcos C.; Miranda, Carlos H.; Santana, Rodrigo C.; Bollela, Valdes R. (Medicina (Ribeirao Preto), 2014)
The different assessment forms are major elements of any teaching and learning process in educational programs, and should be considered as a core component to be planned and implemented in all curriculums, especially in the health professions education. A regular and qualified students’ assessment is closely related to competence and skills of the professionals that will be delivered to society. In this context, formative assessment and well-trained staff to provide effective and regular feedback are essentials in the formation of the future generation of health professionals. This article focuses primarily on formative assessment, feedback and debriefing.